Polyphyllin I suppresses the gastric cancer growth by promoting cancer cell ferroptosis - Zheng, Fang; Wang, Yeshu; Zhang, Qunfang; Chen, Qiuyuan; Liang, Chun-Ling; Liu, Huazhen; Qiu, Feifei; Chen, Yuchao; Huang, Haiding; Lu, Weihui; Dai, Zhenhua (Frontiers in Pharmacology, 2023)
Background Ferroptosis is a new form of regulated cell death characterized by the accumulation of iron-dependent lipid peroxides and membrane damages. Recent studies have identified an important role for cancer cell ferroptosis in antitumor therapy. On the other hand, polyphyllin I (PPI) has been reported to exert antitumor effects on some types of cancers. However, it remains unknown whether or not PPI regulates cancer cell ferroptosis. Methods Two types of human gastric cancer cells (AGS and MKN-45) were used to establish tumor xenograft models in nude mice that were treated with polyphyllin I (PPI) to observe tumor growth, while cells also were cultured for in vitro studies. Ferroptosis, based on the intracellular ROS/lipid ROS production and accumulation of ferrous ions, was detected using a fluorescence microscope and flow cytometer, while the expression of NRF2/FTH1 was measured using Western blotting assays. Results Here we found that PPI inhibited the gastric cancer growth in vivo and in vitro while increasing the intracellular reactive oxygen species (ROS) /lipid peroxides and ferrous ions in the gastric cancer cells. PPI also decreased the levels of nuclear factor erythroid 2-related factor 2 (NRF2) and ferritin heavy chain 1 (FTH1) in gastric cancer cells in vitro. Moreover, liproxstain-1, an inhibitor of cell ferroptosis, mostly reversed the cell ferroptosis and tumor growth arrest induced by PPI. Finally, the effects of PPI on cancer cell ferroptosis were diminished by the overexpression of NRF2. Conclusions For the first time, our results have demonstrated that PPI exerts its antitumor activity on the gastric cancer by, at least partially, inducing cancer cell ferroptosis via regulating NRF2/FTH1 pathway. These findings may be implicated for clinical replacement therapy of the gastric cancer.